2016
DOI: 10.1115/1.4033793
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Transport Properties of NaCl–KCl–ZnCl2 Eutectic Salts for New Generation High-Temperature Heat-Transfer Fluids

Abstract: Three eutectic salts from a system of halide salts NaCl–KCl–ZnCl2 were chosen for detailed study of thermal and transport properties with the objective of developing a next generation high-temperature heat-transfer fluid (HTF) for concentrated solar thermal power (CSP) technology. The acceptable range of the working temperatures for the HTF is from below 250 °C to at least 800 °C. The tested properties are presented here for the three candidate eutectic salts, including melting point, heat of fusion, heat capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(30 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…An in-house developed density meter based on the Archimedean law was employed to conduct the experimental test for the density of MgCl 2 -KCl eutectic molten salt. The calibration of this device was completed in previous work [15]. The density of pure NaCl and KCl were measured using this system at 1200 C, and the difference is less than 1% when compared to data published in literature.…”
Section: Differential Scanning Calorimetry Test For Meltingmentioning
confidence: 98%
See 2 more Smart Citations
“…An in-house developed density meter based on the Archimedean law was employed to conduct the experimental test for the density of MgCl 2 -KCl eutectic molten salt. The calibration of this device was completed in previous work [15]. The density of pure NaCl and KCl were measured using this system at 1200 C, and the difference is less than 1% when compared to data published in literature.…”
Section: Differential Scanning Calorimetry Test For Meltingmentioning
confidence: 98%
“…The studies about molten salts for many years have found that mixing different salts to form a eutectic system is a viable approach to lower the melting point and hold the high boiling temperature in the meantime. For example, eutectic nitrate molten salts were employed as HTF which could operate at temperatures as high as 550 C [15].…”
Section: Chloride Molten Salts For Heat Transfer and Thermal Storage mentioning
confidence: 99%
See 1 more Smart Citation
“…Room to intermediate temperature TES has yet to identify an ideal system with both high gravimetric and volumetric energy densities . The state‐of‐the‐art large‐scale TES is based on molten salts, mostly solar salts (60 wt% NaNO 3 –40 wt% KNO 3 mixture) that have the stable liquid phase within the temperature window of 228 to 650 °C . Development of future TES systems with higher hot‐side temperature requires the solutions to a host of material issues, including suitable TES media (e.g., eutectic halide molten salts, liquid metals, and thermochemical reactions), as well as chemically stable and thermally insulating containment materials that interact with them …”
Section: Introductionmentioning
confidence: 99%
“…For example, the recent technology development on solar [31,[36][37][38] recently developed a chloride salt mixture (NaCl 7.5 wt%-KCl 23.9 wt%-ZnCl 2 68.6 wt%), its melting temperature is about 850 C, while its viscosity is only 0.325 Pa s at 300 C. The cost of this ternary chloride salt mixture is expected to be below 1 $/kg.…”
Section: Application Of Molten Salts As Heat Transfer Fluid In Concenmentioning
confidence: 99%